Fecal Microbiota Functional Gene Effects Related to Single-Dose Antibiotic Treatment of Travelers' Diarrhea. (28th May 2021) - Johnson, Ryan C; Van Nostrand, Joy D; Tisdale, Michele; Swierczewski, Brett; Simons, Mark P; Connor, Patrick; Fraser, Jamie; Melton-Celsa, Angela R; Tribble, David R; Riddle, Mark S
Abstract: Background: Travelers' diarrhea (TD) is common among military personnel deployed to tropical and subtropical regions. It remains unclear how TD and subsequent antibiotic treatment impact the resident microflora within the gut, especially given increased prevalence of antibiotic resistance among enteric pathogens and acquisition of multidrug-resistant organisms. We examined functional properties of the fecal microflora in response to TD, along with subsequent antibiotic treatment. Methods: Fecal samples from US and UK military service members deployed to Djibouti, Kenya, and Honduras who presented with acute watery diarrhea were collected. A sample was collected at acute presentation to the clinic (day 0, before antibiotics), as well as 7 and/or 21 days following a single dose of antibiotics (azithromycin [500 mg], levofloxacin [500 mg], or rifaximin [1650 mg], all with loperamide). Each stool sample underwent culture and TaqMan reverse transcription polymerase chain reaction analyses for pathogen and antibiotic resistance gene detection. Purified DNA from each sample was analyzed using the HumiChip3.1 functional gene array. Results: In total, 108 day 1 samples, 50 day 7 samples, and 94 day 21 samples were available for analysis from 119 subjects. Geographic location and disease severity were associated with distinct functional compositions of fecal samples. There were no overt functional differences between pre- and postantibiotic treatment samples, nor was there increased acquisition of antibiotic resistance determinants for any of the antibiotic regimens. Conclusions: These results indicate that single-dose antibiotic regimens may not drastically alter the functional or antibiotic resistance composition of fecal microflora, which should inform clinical practice guidelines and antimicrobial stewardship. Clinical Trials Registration Number: NCT01618591.